2020
DOI: 10.1038/s41526-019-0091-2
|View full text |Cite
|
Sign up to set email alerts
|

Spaceflight and simulated microgravity conditions increase virulence of Serratia marcescens in the Drosophila melanogaster infection model

Abstract: While it has been shown that astronauts suffer immune disorders after spaceflight, the underlying causes are still poorly understood and there are many variables to consider when investigating the immune system in a complex environment. Additionally, there is growing evidence that suggests that not only is the immune system being altered, but the pathogens that infect the host are significantly influenced by spaceflight and ground-based spaceflight conditions. In this study, we demonstrate that Serratia marces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 61 publications
1
44
0
Order By: Relevance
“…Serratia ureilytica species were found from extreme environmental habitats (Filippidou et al 2019). Drosophila melanogaster had known to be a source of microbial association host, Serratia was included (Chambers et al 2019;Gilbert et al 2020). Prodigiosin was a red pigment which was the characteristic of this genus (Azman et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Serratia ureilytica species were found from extreme environmental habitats (Filippidou et al 2019). Drosophila melanogaster had known to be a source of microbial association host, Serratia was included (Chambers et al 2019;Gilbert et al 2020). Prodigiosin was a red pigment which was the characteristic of this genus (Azman et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…production of lipases) than the baseline (Sugita et al 2016). Moreover astronauts have shown disorders in their immune system upon spaceflight (Gilbert et al 2020).…”
Section: Space Travel Affects the Skin And Immune Systemmentioning
confidence: 99%
“…Moreover astronauts have shown disorders in their immune system upon spaceflight (Gilbert et al . 2020).…”
Section: Space Travel Affects the Skin And Immune Systemmentioning
confidence: 99%
“…Very recently, Gilbert et al . (2020) found that Serratia marcescens was more lethal to Drosophila melanogaster on the ISS than in ground-based controls and suggested that spaceflight induces a physiological change leading to increased virulence in the pathogen. In contrast, the virulence of clinical pathogens ( Listeria monocytogenes , methicillin-resistant S. aureus (MRSA), Enterococcus faecalis and C. albicans ) against larvae and adult Caenorhabditis elegans reduced in the space environment (Hammond et al ., 2013).…”
Section: Experiments In Space and Ground-based Space Simulation Facilmentioning
confidence: 99%